IMPLEMENTASI THIN CLIENT NETWORK BERBASIS WINDOWS DAN LINUX (STUDI KASUS PADA STMIK KHARISMA MAKASSAR) - Syaiful Rahman (Jurnal Sistem Informasi dan Komputer (JSIKOM), 2020)
Abstract: The objetive of this research was designing and implementing a windows-and-linux-based thin client network to obtain a specification of thin client network which can used by educational institution as tools of learning. This research began studying concept of thin client network and its various and usage, designing its appropriate architecture, implementing and evaluating the architecure to obtain information related to the specification. The analysis result showed that cost of implementation of thin client network needs only quarter of total cost of the standard network. The evaluation of Windows Terminal Server which involving 60 users showed that average of total of processor time was 16.25% and average of processor queue length was 0. While the evaluation of Linux Terminal Server showed that average of respon time of the server was 5 second and average of idle time of processor was 97%. The reasearch was concluded that performance of both server appropriate for thin client network..